Good guy with a gun [videorecording (DVD)] - Mossman, John; Nolan, Beck; Bedwell, Tiffany; Cain, Jack (Freestyle Digital Media, 2024)
In this taut thriller, after the violent death of his father, teenage Will and his mother move to a small town. Angry and insecure, Will is introduced to the local gun culture, further fracturing his relationship with his mother and complicating his grief.